The Effect of Buying and Selling Financing and Profit Sharing Financing on Financial Performance at BPRS Bhakti Sumekar - Fadali Rahman; Puji Handayati; Sonhaji (International Journal of Integrative Sciences, 2023)
Buying and selling financing is a form of financing made by banks or other financial institutions to their customers to buy certain goods or assets. Profit-sharing financing is a form of financing carried out by banks or other financial institutions to their customers by sharing profits or business results obtained from projects or business activities funded by said bank or financial institution. This study aims to analyze the effect of buying and selling financing and profit sharing financing on the financial performance of BPRS Bhakti Sumekar. Research design in this writing is library research (library research), namely by looking for research data or information through reading scientific journals, reference books, published financial reports and publication materials available as support in this writing. In the nature of this research using quantitative research, the quantitative method is a research method based on the philosophy of positivism used to examine certain populations or samples. Data were obtained from the financial statements of BPRS Bhakti Sumekar for the last four years from 2017 to 2020. Regression analysis was used to evaluate the effect of the two factors on financial performance, which was measured using financial ratios such as ROA. The results of the analysis show that buying and selling financing and profit sharing financing have a significant influence on financial performance at BPRS Bhakti Sumekar. In this case, profit sharing financing has a greater influence than buying and selling financing. These findings provide important implications for the management of BPRS Bhakti Sumekar in managing the financing portfolio and improving financial performance